Changes in the Physical and Mechanical Properties of Clay Soil Due to Stabilization with Lime - Ferly Indra Putra; Kiagus Ahmad Roni; Sri Martini (International Journal of Information Engineering and Science, 2025)
Clay soil stabilization is a crucial process to enhance the soil's bearing capacity and stability, making it more suitable for construction purposes. Stabilizing clay soils improves their mechanical properties, reduces swelling, and increases their load-bearing capacity, which is essential for the foundation of various structures. This study aims to investigate the effect of lime (CaO) addition and curing time on the physical properties of clay soil, particularly focusing on unconfined compressive strength (qu) and overall soil stability. The experimental methodology involved applying different percentages of lime content (ranging from 3% to 7%) and varying curing times (7, 14, and 28 days). The soil samples were tested for their unconfined compressive strength after each combination of lime content and curing duration. The results indicated that the addition of 5% lime (CaO) and curing for 14 days led to a significant improvement in the unconfined compressive strength by 153.3%, compared to the untreated clay soil. Furthermore, increasing the curing time beyond 14 days did not show substantial improvements in strength, suggesting that 14 days is the optimal curing period for this combination. The study also highlighted that the lime treatment not only enhanced the mechanical properties but also reduced the plasticity of the clay, making it more stable and easier to handle during construction. Based on these findings, it can be concluded that the appropriate combination of lime content and curing time plays a significant role in improving the stability of clay soils. This research provides valuable insights into optimizing soil stabilization techniques, offering an effective solution for enhancing soil properties for engineering applications